Pengaruh model game based learning berbantuan media kubus magic terhadap kemampuan berhitung siswa kelas I - Laila Mukaromah; Ari Suryawan; Sukma Wijayanto (Borobudur Educational Review, 2021)
This study aims to determine the effect of game-based learning model assisted by magic cube media on the numeracy ability of grade I students of MI NA Trasan Bandongan, Magelang District. This research method is pre-experimental with a one group pre-test post-test design model. The research subject were selected using a total sampling technique using the entire class 1 population. The sample used is 20 students. Method of data collection was carried out using a multiple choice test totaling 25 questions. The multiple-choice instrument validation test uses the product moment formula, while reliability test using Cronbach’s alpha formula by SPSS for Windows version 25. Data analysis using non-parametric statistic technique that is Wilcoxon sign rank test by SPSS for Windows version 25. The results of this research shows game-based learning model assisted by magic cube media has a positive effect on the numeracy ability of grade 1 students. This is evidenced from the results of the Wilcoxon sign rank test analysis with the probability of Asymp. Sig. (2-tailed) 0,000<0,05. Based on the results of the analysis and discussion, there is a difference in the average score on the posttest results as musch as 91 and the pretest results with an average score of 73. The results of this research can be conclude that the use of game-based learning model assisted by magic cube media has a positive effect on the numeracy ability of grade 1 students.